Lo stadio polivalente: usi eterogenei di un edificio antico - Cecconi, Niccolò (O T I V M, 2023)
The stadium was the building mainly used for sporting competitions. However, the sources (archaeological, historical, and epigraphical) indicate that this building was used also in different ways. To verify this heterogeneous use of the stadium in the Greek and Roman world, the study in three parts is divided: the first concerns the sources; the second looks at the stadium as a component of a multifunctional urban and topographical context; the third analyses some multifunctional devices of the ancient stadia.